Food and sustainability : communication, PR, and the culture of responsibility - Topić-Rutherford, Martina; Zeman, Marija Geiger (Emerald Publishing Limited, 2026)
Understanding how food is communicated through media and campaigns is key to shaping sustainable food practices. Food and Sustainability presents a comprehensive, interdisciplinary approach to food studies by gathering voices from communications, sociology, ethnology, and even fashion. This edited collection maps the intersections of food, sustainability, and responsibility, with contributions that analyse professional chefs, media portrayals, and food security issues. The first section explores the nuances of food sustainability in media, gender dynamics, and lived experiences, while the second focuses on how public relations advances a culture of responsibility across societal contexts--from health campaigns to corporate practices and educational efforts. With its dual focus on empirical analysis and innovative methodologies, this study expands both theoretical and practical approaches to food communication in a changing world.